ACHIEVEMENT STUDENT SELECTION SYSTEM USING THE SAW METHOD AND WSM METHOD - Rizal Furqan Ramadhan (LPPM Nusa Mandiri, 2024)
Higher education is an academic establishment that prepares students for the workforce by imparting both theoretical knowledge and practical skills, shaping them into educated individuals ready for professional life. One way to encourage increased student competence is to implement a selection of students with good achievements in terms of academic and non-academic abilities. The assessment of outstanding students has been widely implemented, but the system needs to be criteria-based. This research develops a Decision Support System, which makes it easier and helpful for the Dean and head of the department to decide on outstanding students. The study used 2 Multi-Criteria methods. The two methods of the applied multi-criteria concept The Simple Additive Weighting and Weighted Sum Model are applied to assess 22 students UIN Sayyid Ali Rahmatullah Tulungagung, enhancing their readiness for the job market by refining their theoretical understanding and practical capabilities through higher education. Students come from 4 different faculties taken randomly. These faculties include tarbiyah, ushuluddin, economics and sharia each semester 6. The outcomes from both techniques exhibit a high level of similarity. MHS8 and MHS10 secure the top two spots, with variations emerging in subsequent rankings when considering the combined criteria of the two methods. Based on the system test results, the system's output using these two methods produces students with achievements in almost the same order, and students with achievements made from the system are in accordance with conditions in the field that these students really have achievements.